5.12.14 Problems 1301 to 1396

Table 5.845: Third and higher order linear ODE

#

ODE

Mathematica

Maple

18954

\[ {}y^{\prime \prime \prime } = x \,{\mathrm e}^{x} \]

18955

\[ {}x^{2} y^{\prime \prime \prime \prime }+1 = 0 \]

18961

\[ {}x^{2} y^{\prime \prime \prime }-4 x y^{\prime \prime }+6 y^{\prime } = 4 \]

18969

\[ {}y^{\prime \prime \prime \prime }+a^{2} y^{\prime \prime } = 0 \]

18970

\[ {}y^{\left (5\right )}-m^{2} y^{\prime \prime \prime } = {\mathrm e}^{a x} \]

18971

\[ {}x^{2} y^{\prime \prime \prime \prime }+a^{2} y^{\prime \prime } = 0 \]

18984

\[ {}\left (x^{3}+x +1\right ) y^{\prime \prime \prime }+\left (3+6 x \right ) y^{\prime \prime }+6 y = 0 \]

18985

\[ {}x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }+x \left (x^{2}+2\right ) y^{\prime }+3 x^{2} y = 2 x \]

18986

\[ {}y^{\prime \prime \prime \prime }-a^{2} y^{\prime \prime } = 0 \]

18988

\[ {}\left (x^{3}-x \right ) y^{\prime \prime \prime }+\left (8 x^{2}-3\right ) y^{\prime \prime }+14 x y^{\prime }+4 y = \frac {2}{x^{3}} \]

18992

\[ {}x y^{\prime \prime \prime }-x y^{\prime \prime }-y^{\prime } = 0 \]

18995

\[ {}y^{\prime \prime \prime } = \sin \left (x \right )^{2} \]

18997

\[ {}y^{\prime \prime \prime }+\cos \left (x \right ) y^{\prime \prime }-2 \sin \left (x \right ) y^{\prime }-y \cos \left (x \right ) = \sin \left (2 x \right ) \]

19001

\[ {}y^{\prime \prime \prime } = f \left (x \right ) \]

19027

\[ {}x^{2} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

19160

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }-y^{\prime }+2 y = 0 \]

19164

\[ {}y^{\prime \prime \prime }+y^{\prime \prime }-5 y^{\prime }+3 y = 0 \]

19166

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+3 y^{\prime }-y = 0 \]

19167

\[ {}y^{\prime \prime \prime \prime }-2 y^{\prime \prime }+y = 0 \]

19168

\[ {}y^{\prime \prime \prime \prime }+8 y^{\prime \prime }+16 y = 0 \]

19169

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+y^{\prime }-5 y = 0 \]

19170

\[ {}2 y^{\prime \prime \prime }-3 y^{\prime \prime }+2 y^{\prime }+2 y = 0 \]

19171

\[ {}y^{\prime \prime \prime \prime }-y = 0 \]

19172

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = 0 \]

19183

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }-y^{\prime }-12 y = \cos \left (4 x \right ) \]

19186

\[ {}y^{\prime \prime \prime }-4 y^{\prime \prime }+5 y^{\prime }-2 = 0 \]

19187

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }-y^{\prime }+y = x \]

19188

\[ {}y^{\prime \prime \prime }-y^{\prime \prime }-6 y^{\prime } = x^{2}+1 \]

19189

\[ {}y^{\prime \prime \prime }+2 y^{\prime \prime }+y^{\prime } = {\mathrm e}^{2 x}+x^{2}+x \]

19190

\[ {}y^{\prime \prime \prime }-3 y^{\prime }+2 y = {\mathrm e}^{x} \]

19194

\[ {}y^{\prime \prime \prime }-7 y^{\prime }-6 y = {\mathrm e}^{2 x} \left (1+x \right ) \]

19195

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime }+y = a \,x^{2}+b \,{\mathrm e}^{-x} \sin \left (2 x \right ) \]

19198

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = x^{2} \cos \left (x \right ) \]

19199

\[ {}y^{\prime \prime \prime \prime }-y = x \sin \left (x \right ) \]

19203

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime }+y = {\mathrm e}^{-\frac {x}{2}} \cos \left (\frac {\sqrt {3}\, x}{2}\right ) \]

19204

\[ {}y^{\left (6\right )}-2 y^{\left (5\right )}+3 y^{\prime \prime \prime \prime }-4 y^{\prime \prime \prime }+3 y^{\prime \prime }-2 y^{\prime }+y = \sin \left (\frac {x}{2}\right )^{2}+{\mathrm e}^{x} \]

19205

\[ {}y^{\prime \prime \prime \prime }+y^{\prime \prime }+16 y = 16 x^{2}+256 \]

19207

\[ {}y^{\prime \prime \prime \prime }+10 y^{\prime \prime }+9 y = 96 \sin \left (2 x \right ) \cos \left (x \right ) \]

19208

\[ {}y^{\left (5\right )}-13 y^{\prime \prime \prime }+26 y^{\prime \prime }+82 y^{\prime }+104 y = 0 \]

19210

\[ {}y^{\prime \prime \prime \prime }+2 y^{\prime \prime }+y = 24 x \cos \left (x \right ) \]

19317

\[ {}x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }-2 y = 0 \]

19318

\[ {}x^{2} y^{\prime \prime \prime }-2 y^{\prime } = 0 \]

19319

\[ {}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+6 x y^{\prime }-6 y = \ln \left (x \right )^{2} \]

19320

\[ {}y^{\prime \prime \prime }-\frac {4 y^{\prime \prime }}{x}+\frac {5 y^{\prime }}{x^{2}}-\frac {2 y}{x^{3}} = 1 \]

19321

\[ {}x^{2} y^{\prime \prime \prime }+x y^{\prime \prime }-4 y^{\prime } = 0 \]

19322

\[ {}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+7 x y^{\prime }-8 y = 0 \]

19324

\[ {}x^{2} y^{\prime \prime \prime }+3 x y^{\prime \prime }+2 y^{\prime } = 0 \]

19335

\[ {}x^{2} y^{\prime \prime \prime }+3 x y^{\prime \prime }+2 y^{\prime } = x \]

19336

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+9 x^{2} y^{\prime \prime }+3 x y^{\prime }+y = 4 x \]

19337

\[ {}x^{3} y^{\prime \prime \prime }+6 x^{2} y^{\prime \prime }+8 x y^{\prime }+2 y = x^{2}+3 x -4 \]

19339

\[ {}x^{3} y^{\prime \prime \prime }-3 x^{2} y^{\prime \prime }+7 x y^{\prime }-8 y = x^{2}+\frac {1}{x^{2}} \]

19340

\[ {}x^{4} y^{\prime \prime \prime \prime }+2 x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-x y^{\prime }+y = x +\ln \left (x \right ) \]

19343

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }-x y^{\prime }+y = x \ln \left (x \right ) \]

19344

\[ {}x^{4} y^{\prime \prime \prime \prime }+6 x^{3} y^{\prime \prime \prime }+9 x^{2} y^{\prime \prime }+3 x y^{\prime }+y = \left (\ln \left (x \right )+1\right )^{2} \]

19350

\[ {}x^{3} y^{\prime \prime \prime }+6 x^{2} y^{\prime \prime }+8 x y^{\prime }+2 y = x^{2}+3 x -4 \]

19351

\[ {}x y^{\prime \prime \prime }+\left (x^{2}-3\right ) y^{\prime \prime }+4 x y^{\prime }+2 y = 0 \]

19360

\[ {}x^{2} y^{\prime \prime \prime }+4 x y^{\prime \prime }+\left (x^{2}+2\right ) y^{\prime }+3 x y = 2 \]

19361

\[ {}x^{5} y^{\left (6\right )}+x^{4} y^{\left (5\right )}+x y^{\prime }+y = \ln \left (x \right ) \]

19362

\[ {}x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }+x \left (x^{2}+2\right ) y^{\prime }+3 x^{2} y = 2 x \]

19364

\[ {}y^{\prime \prime \prime } = f \left (x \right ) \]

19369

\[ {}x^{3} y^{\prime \prime \prime } = 1 \]

19371

\[ {}y^{\prime \prime \prime } \csc \left (x \right )^{2} = 1 \]

19384

\[ {}x^{2} y^{\prime \prime \prime }-4 x y^{\prime \prime }+6 y^{\prime } = 4 \]

19389

\[ {}x y^{\prime \prime \prime }-x y^{\prime \prime }-y^{\prime } = 0 \]

19409

\[ {}a^{2} y^{\prime \prime \prime \prime } = y^{\prime \prime } \]

19410

\[ {}y^{\prime \prime \prime \prime }+a^{2} y^{\prime \prime } = 0 \]

19411

\[ {}y^{\left (5\right )}-n^{2} y^{\prime \prime \prime } = {\mathrm e}^{a x} \]

19412

\[ {}x^{2} y^{\prime \prime \prime \prime }+a^{2} y^{\prime \prime } = 0 \]

19413

\[ {}x^{2} y^{\prime \prime \prime \prime } = \lambda y^{\prime \prime } \]

19414

\[ {}n \,x^{3} y^{\prime \prime \prime } = -x y^{\prime }+y \]

19423

\[ {}a y^{\prime \prime \prime } = y^{\prime \prime } \]

19424

\[ {}x^{2} y^{\prime \prime \prime \prime }+1 = 0 \]

19425

\[ {}y^{\prime \prime \prime } = \sin \left (x \right )^{2} \]

19434

\[ {}\left (x^{3}-4 x \right ) y^{\prime \prime \prime }+\left (9 x^{2}-4\right ) y^{\prime \prime }+18 x y^{\prime }+6 y = 6 \]

19441

\[ {}y^{\prime \prime \prime }-x y^{\prime \prime }-y^{\prime }+x y = 0 \]

19442

\[ {}x^{3} y^{\prime \prime \prime }+x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

19530

\[ {}y^{\prime \prime \prime \prime }-y^{\prime \prime \prime }-9 y^{\prime \prime }-11 y^{\prime }-4 y = 0 \]

19531

\[ {}y^{\prime \prime \prime }-8 y = 0 \]

19532

\[ {}y^{\prime \prime \prime }-2 y^{\prime \prime }+y^{\prime } = {\mathrm e}^{-x} \]

19534

\[ {}y^{\prime \prime \prime }+y = \left (1+{\mathrm e}^{x}\right )^{2} \]

19536

\[ {}y^{\prime \prime \prime }+a^{2} y^{\prime } = \sin \left (a x \right ) \]

19537

\[ {}y^{\prime \prime \prime }-3 y^{\prime \prime }+4 y^{\prime }-2 y = {\mathrm e}^{x}+\cos \left (x \right ) \]

19539

\[ {}y^{\prime \prime \prime }+3 y^{\prime \prime }+2 y^{\prime } = x^{2} \]

19578

\[ {}x^{4} y^{\prime \prime \prime }+2 x^{3} y^{\prime \prime }-x^{2} y^{\prime }+x y = 1 \]

19580

\[ {}x^{3} y^{\prime \prime \prime }-x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = x^{2}+3 x \]

19581

\[ {}x^{3} y^{\prime \prime \prime }+6 x^{2} y^{\prime \prime }+4 x y^{\prime }-4 y = 0 \]

19582

\[ {}x^{3} y^{\prime \prime \prime }+3 x^{2} y^{\prime \prime }+x y^{\prime }+y = 0 \]

19584

\[ {}x^{3} y^{\prime \prime \prime }+2 x^{2} y^{\prime \prime }+2 y = 10 x +\frac {10}{x} \]

19586

\[ {}\left (2 x -1\right )^{3} y^{\prime \prime \prime }+\left (2 x -1\right ) y^{\prime }-2 y = 0 \]

19588

\[ {}16 \left (1+x \right )^{4} y^{\prime \prime \prime \prime }+96 \left (1+x \right )^{3} y^{\prime \prime \prime }+104 \left (1+x \right )^{2} y^{\prime \prime }+8 \left (1+x \right ) y^{\prime }+y = x^{2}+4 x +3 \]

19593

\[ {}\left (x^{2}+x +1\right ) y^{\prime \prime \prime }+\left (3+6 x \right ) y^{\prime \prime }+6 y^{\prime } = 0 \]

19594

\[ {}\left (x^{3}-x \right ) y^{\prime \prime \prime }+\left (8 x^{2}-3\right ) y^{\prime \prime }+14 x y^{\prime }+4 y = \frac {2}{x^{3}} \]

19595

\[ {}y^{\prime \prime \prime }+\cos \left (x \right ) y^{\prime \prime }-2 \sin \left (x \right ) y^{\prime }-y \cos \left (x \right ) = \sin \left (2 x \right ) \]

19602

\[ {}y^{\prime \prime \prime } = x \,{\mathrm e}^{x} \]

19611

\[ {}y^{\prime \prime \prime \prime }-a^{2} y^{\prime \prime } = 0 \]

19638

\[ {}y^{\prime \prime \prime }-6 y^{\prime \prime }+11 y^{\prime }-6 y = {\mathrm e}^{2 x} \]